2021
DOI: 10.3390/ijms22126173
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cancer Metabolism by Deubiquitinating Enzymes: The Warburg Effect

Abstract: Cancer is a disorder of cell growth and proliferation, characterized by different metabolic pathways within normal cells. The Warburg effect is a major metabolic process in cancer cells that affects the cellular responses, such as proliferation and apoptosis. Various signaling factors down/upregulate factors of the glycolysis pathway in cancer cells, and these signaling factors are ubiquitinated/deubiquitinated via the ubiquitin–proteasome system (UPS). Depending on the target protein, DUBs act as both an onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 185 publications
(193 reference statements)
2
31
0
Order By: Relevance
“…In general, TGF-β shifts metabolism from mitochondrial oxidative phosphorylation toward a ketogenic metabolism, and EMT and EndMT, which are induced by TGF-β, can shift tumor and endothelial cell metabolism from oxidative phosphorylation toward anaerobic glycolysis (Angioni et al, 2021). Such a switching of the tumor metabolism from oxidative phosphorylation to anerobic glycolysis and lactate production was first described by Warburg (Warburg et al, 1927;Kim and Baek, 2021).…”
Section: Tumor Metabolism-a Symbiotic Relationship Of Parenchymal and Mesenchymal Cellsmentioning
confidence: 99%
“…In general, TGF-β shifts metabolism from mitochondrial oxidative phosphorylation toward a ketogenic metabolism, and EMT and EndMT, which are induced by TGF-β, can shift tumor and endothelial cell metabolism from oxidative phosphorylation toward anaerobic glycolysis (Angioni et al, 2021). Such a switching of the tumor metabolism from oxidative phosphorylation to anerobic glycolysis and lactate production was first described by Warburg (Warburg et al, 1927;Kim and Baek, 2021).…”
Section: Tumor Metabolism-a Symbiotic Relationship Of Parenchymal and Mesenchymal Cellsmentioning
confidence: 99%
“…Deubiquitination is the reverse process of ubiquitination, is mediated by DUBs. DUBs are the most studied DCEs comprising of: ubiquitin-specific proteases (USP), ubiquitin C-terminal hydrolases (UCH), otubain domain ubiquitin-binding proteins (OTU), Machado–Joseph disease protein domain proteases (MJD), the MIU-containing novel DUB family (MINDY), the monocyte chemotactic protein-induced proteins (MCPIP) families, the Zn-finger and UFSP domain protein (ZUFSP) family, the permuted papain fold peptidase of dsDNA viruses and eukaryotes (PPPDE), and the Jab1/MPN domain-associated metalloisopeptidase (JAMM) family [ 84 , 85 ]. Depending on their enzymatic cleavage mechanism, DUBs are classified into two types: cysteine protease and metalloprotease.…”
Section: Deubiquitination In Amlmentioning
confidence: 99%
“…In this malignant mechanism, the MYC oncogene contributes to alterations in cellular metabolism to facilitate tumorigenesis by altering nucleotide metabolism and DNA replication induced by the attenuated expression of E2F1; hypoxia-inducible transcription factor 1; lactate dehydrogenase A; and several microRNAs, such as miR-23a/b, to increase the protein expression of glutaminase [15]. In addition to the regulation of gene expression at the transcriptional level, research has revealed the significance of the ubiquitin-proteasome system (UPS), which controls various signaling factors in the glycolysis pathway via ubiquitination or deubiquitination [16]. As a result of UPS, deubiquitination acts as either a tumor-promoting oncoprotein or as a tumor-restricting suppressor protein [16].…”
Section: Oncogenes and Tme-driven Metabolism Alterationsmentioning
confidence: 99%
“…In addition to the regulation of gene expression at the transcriptional level, research has revealed the significance of the ubiquitin-proteasome system (UPS), which controls various signaling factors in the glycolysis pathway via ubiquitination or deubiquitination [16]. As a result of UPS, deubiquitination acts as either a tumor-promoting oncoprotein or as a tumor-restricting suppressor protein [16].…”
Section: Oncogenes and Tme-driven Metabolism Alterationsmentioning
confidence: 99%